Pembuatan Game Labirin Bola Dengan Pemecahan Masalah Aritmatika Berbasis Android - Restuyoda, Raka; Candra, Feri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Arithmetic is a branch of mathematics that deals with 4 basic operations, namely addition, subtraction, multiplication and division. Arithmetic lessons are very important because this knowledge will be used until adulthood for daily activities, but children or elementary school students have difficulty solving arithmetic problems. Based on research conducted by Phonapichat (2014) on grade 5 and 6 elementary school students, it is known that there are five student difficulties in solving math problems, some of which are, 1) Every student who does not understand the problem, they tend to guess the answer without thinking about it first. 2) Students are impatient and do not like to read math problems. 3) Students do not like to read very long problems. It is hoped that by using video games as a medium for learning arithmetic problem solving, children will put more effort into solving arithmetic problems. Because of the research conducted by (Norlita et al., 2020) obtained data from 75 respondents of elementary school students in grades 5 and 6 who play games on gadgets by 100%, often play games on gadgets by 45.3%, and play games more than 2 hours by 41.3%.. The author uses a maze so that the player cannot just choose a path because the player will be hit by a trap that has been prepared if the wrong path is chosen. To complete the level of the game, the player must get to the end point of the level. But to get to the end point, players must find the right path by answering arithmetic questions correctly. Game testing is performed with blackbox and usability methods.Keywords : Maze Game, Arithmetic Educational Game, Android